Consumer choice determinants of online intermediary tourism platforms - Elżbieta Wąsowicz-Zaborek (International Journal of Management and Economics, 2022)
The article investigates determinants of usage intention (IU) of online travel agencies' (OTAs) services by consumers and their propensity for word-of-mouth (WOM). The determinants represent two groups of factors: (1) items reflecting the perceived quality of OTAs' platforms (PQ) and (2) those corresponding to transaction quality (CST). The survey was conducted with the CAWI method on a representative net sample of 591 Polish OTA users. Statistical analysis involved building a covariance-based structural equation model to map out causal relationships between latent variables and test research hypotheses. The findings indicate that both groups of factors (PQ and CST) have a statistically significant positive effect on both IU and WOM. However, the impact of CST was found to be slightly weaker. Interestingly, there were no moderating effects from the respondents' age, income, and education. The only demographical characteristic of issue was sex, which revealed different regression patterns between men and women.
Keywords: M31; Z33; 650; online travel agencies; structural equation model; tourist behavior; usage intention; word-of-mouth intention